Mechanical Characterization of Reduced Graphene Oxide Using AFM. (2nd January 2019) - Teklu, Alem; Barry, Canyon; Palumbo, Matthew; Weiwadel, Collin; Kuthirummal, Narayanan; Flagg, Jason
Abstract : Nanoindentation coupled with Atomic Force Microscopy was used to study stiffness, hardness, and the reduced Young's modulus of reduced graphene oxide. Oxygen reduction on the graphene oxide sample was performed via LightScribe DVD burner reduction, a cost-effective approach with potential for large scale graphene production. The reduction of oxygen in the graphene oxide sample was estimated to about 10 percent using FTIR spectroscopic analysis. Images of the various samples were captured after each reduction cycle using Atomic Force Microscopy. Elastic and spectroscopic analyses were performed on the samples after each oxygen reduction cycle in the LightScribe, thus allowing for a comparison of stiffness, hardness, and the reduced Young's modulus based on the number of reduction cycles. The highest values obtained were after the fifth and final reduction cycle, yielding a stiffness of 22.4 N/m, a hardness of 0.55 GPa, and a reduced Young's modulus of 1.62 GPa as compared to a stiffness of 22.8 N/m, a hardness of 0.58 GPa, and a reduced Young's modulus of 1.84 GPa for a commercially purchased graphene film made by CVD. This data was then compared to the expected values of pristine single layer graphene. Furthermore, two RC circuits were built, one using a parallel plate capacitors made of light scribed graphene on a kapton substrate (LSGC) and a second one using a CVD deposited graphene on aluminum (CVDGC). Their RC time constants and surface charge densities were compared.